English placement test: baseline results of new intake students - Abdul Malik, Faridah; Ahmad, Lily Azlina; Salleh, Nellia Lizrina (Research & Scientific Innovation Society, 2025)
An English placement test (EPT) is an essential component of any foundation programme. It helps place students into their suitable language proficiency level so that they do not spend time learning materials below or above their levels. It also helps curriculum developers and teachers to prepare teaching materials to students of similar levels. This study examined the difference in performance between students from various course language groups of the International Islamic University Malaysia (IIUM) based on the English Placement Test (EPT) results from 2019-2023. 5729 new undergraduate students were analysed based on the Writing and Reading components of the EPT examinations. The correlation between the two components was then investigated, adjusting for the sex of the students involved. A 2-way ANOVA was conducted to determine the mean difference for writing and reading bands according to group. An ANCOVA test was then conducted to determine the correlation between the two components. It was found that overall, the English Major group showed a 0.687 mean difference in band compared to the English Medium group while the Non-English Major group showed a -0.3 mean difference in band in comparison. A positive correlation was found where an increase of 0.625 in reading band was observed for every increase in writing band. Furthermore, males generally performed slightly lower than females, but their performance showed to improve as their scores increased. In conclusion, this study serves as a foundational baseline for further studies on the EPT results in IIUM.